Case Report: Clinical Analysis of Fulminant Mycoplasma pneumoniae Pneumonia in Children - Zhang, Tongqiang; Han, Chunjiao; Guo, Wei; Ning, Jing; Cai, Chunquan; Xu, Yongsheng (Frontiers in Pediatrics, 2021)
FMPP accounts for 0.5–2% of all MPP cases which is considered as MPP combined with severe complications such as hypoxemia, acute respiratory distress syndrome or acute respiratory failure. It primarily affects young adults with no underlying disease. Although some studies have proved the severity of FMPP, the details about clinical diagnosis and treatment of FMPP in children has been rarely reported. In our report, we described three cases who suffered from FMPP. These children not only developed acute lung injury and multiple organ involvement within 7 days of treatment, but was also found plastic bronchitis by bronchoscopy. Finally, all patients were treated successfully with azithromycin, glucocorticoid and bronchoscopy lavage. We conclude that our report would contribute to raise awareness regarding FMPP which may occur at a younger age with faster disease progression and common extrapulmonary manifestations. It also reinforces the importance of early identification and prompt intervention to save children's life and reduce sequelae. In addition, further studies are needed about mechanism and etiology of FMPP.